Genomic full‐length sequence of two new HLA‐C alleles, HLA‐C*04:239 and HLA‐C*05:137. (26th October 2016) - Santos, S.; Arroyo, J. L.; Eguizabal, C.; Balas, A.; Vicario, J. L.
Abstract : Two novel HLA‐C alleles, C*04:239 and C*05:137, were characterized in Spanish individuals.